Denotasi dan Konotasi dalam Lirik Lagu Kalam Einih Kajian Semantik - Heeral Manna; Umi Kulsum (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This study is motivated by the importance of understanding song lyrics as a form of linguistic and cultural expression rich in meaning, particularly within the context of contemporary Arabic music. The song “Kalam Einih” by Sherine Abdul Wahab was selected for its deep emotional and symbolic content, as well as its combination of fusha and amiyah Arabic. This research aims to identify and analyze the denotative and connotative meanings found in the lyrics, using the semantic theory of Chaer. The method applied is descriptive qualitative with note-taking and content analysis techniques, supported by expert judgment validation. The findings reveal that the lyrics contain literal meanings that express love explicitly, and connotative meanings that imply emotional depth through the symbolism of eye contact. This study confirms that song lyrics can represent cultural and psychological realities in an implicit manner. The results contribute to the development of semantic studies in musical contexts and enrich the linguistic scholarship on modern Arabic expression.